Konsep Akhlak dalam QS. Al Ahzab 33:21 - Studi Komparasi antara Tafsir Ibnu Katsir dan Tafsir Al-Munīr Karya Wahbah Az-Zuhailī - Cholid Ma'arif; Fathur Rofi'i; Muhammad Muhammad (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACTION This study aims to analyze the interpretation of Surah al-Aḥzāb, 33:21, which raises the concept of uswah ḥasanah (good example) in the Prophet Muhammad (peace be upon him) according to two prominent commentators, Ibn Kathir and Wahbah al-Zuḥaylī. To this end, the researcher positions the concept of morality as the formal object and the verse in question as the material object. This study uses a qualitative approach with library research and comparative analysis to explore the moral messages in the interpretations of these two figures. Ibn Kathir emphasizes the historical and exemplary aspects in the context of warfare and the faith of the Companions, while Wahbah al-Zuḥaylī provides a normative interpretation applicable to contemporary Muslims. The results show that despite differences in style and approach, both emphasize the importance of embracing the Prophet Muhammad (peace be upon him) as a model for moral development. The relevance of this interpretation is significant in addressing the challenges of moral degradation in the modern era, particularly in holistic moral education. This study recommends integrating the moral values ​​of the Prophet Muhammad (peace be upon him) into formal and non-formal education, continually adapting to changing times. Keywords : Concept of Morals, QS. Al-Ahzab: 33:21, Tafsir Ibn Kathir, Tafsir Al-Munir